Composición química y contenido de fenoles totales en aceites esenciales de muña Minthostachys setosa Briq Epl y anís Pimpinella anísum L. - Chaquilla Quilca y Cols., Guadalupe (2019)
The chemical composition and the content of total phenols present in essential oils extracted from muña (Minthostachys setosa Briq Epl) and anise (Pimpinella anísum L.) collected in the Apurimac region, Perú were determined. Analyses of GC-MS of the essential oil of muña has reported the presence of about 18 different volatile compounds such as isomentona 39%, pulegona 32%, isomentona 6% and timol 5%, whereas in case of anise it has been detected mainly anetol 96% and other minor compounds. The content of total phenols in samples was determined by the method of Folin Ciocalteu and expressed as mg gálic acid/g essential oil. Results showed that the content of total phenols in muña and anise were 253.65 mg y 73.50 mg gálic acid/g oil respectively. From these results, the essential oil of muña shows a better antioxidant activity and it could be used as a natural antioxidant in food preparation.